Interaction types in distance learning : Experiences and perspectives of Austrian EFL student teachers (Pedagogical Horizons, 2021)
The present paper examined how 107 Austrian EFL student teachers experienced online interaction types in distance learning during the COVID-19 university lockdown in March 2020. Four different online interaction types (learner-self, learner-interface, learner-content, and learner-support) were derived from the pertinent literature and converted into both open and closed online questionnaire items (Ally, 2011; Boling, Hough, Krinsky, Saleem, & Stevens, 2012; Zheng, Lin, & Kwon, 2020). Using a mixed-methods convergent parallel research design, closed items were examined quantitatively, with a focus on response distributions and the homogeneity of the scales representing the four types; a qualitative analysis of the open items complemented the quantitative results and explored response patterns and response categories in more detail. Thus, the interpretations are based on a parallelly converging evaluation of both data types. Triangulation of the results suggests that student teachers regard regular guidance by instructors and a shift from teaching to learning materials including cognitively demanding tasks as crucial for their learning process. Whereas student teachers reported positive experiences with regard to learner-support interaction, peer interaction was reported as deficient. The paper concludes with a discussion of implications for online course development and delivery as well as avenues for future research.
Keywords: online interaction; EFL teacher training; distance teaching; mixed-methods convergent parallel design